1991
DOI: 10.1029/91ja01703
|View full text |Cite
|
Sign up to set email alerts
|

The helium abundance of Neptune from Voyager measurements

Abstract: Voyager radio occultation and infrared spectrometer measurements are used to obtain an estimate of the helium abundance in the atmosphere of Neptune. It is found that the shape of the measured spectrum cannot be well matched by spectra calculated from atmospheric models that include only gaseous opacity. The most plausible explanation of the observed spectral shape appears to require the existence of an additional opacity source associated with clouds or hazes. The data can be fit with either a tropospheric or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 53 publications
5
22
0
Order By: Relevance
“…The derived helium abundance, 14.9 +1.7 −2.2 %, confirms, with smaller error bars, previous determination obtained from the combined analysis of Voyager-2 IRIS and radio occultation experiment (Conrath et al, 1991). This result is consistent with the protoplanetary estimate of the helium abundance, as expected from the internal models of Neptune which predict no differenciation (Marley, 1999).…”
Section: Tropospheric Compositionsupporting
confidence: 90%
“…The derived helium abundance, 14.9 +1.7 −2.2 %, confirms, with smaller error bars, previous determination obtained from the combined analysis of Voyager-2 IRIS and radio occultation experiment (Conrath et al, 1991). This result is consistent with the protoplanetary estimate of the helium abundance, as expected from the internal models of Neptune which predict no differenciation (Marley, 1999).…”
Section: Tropospheric Compositionsupporting
confidence: 90%
“…Figure 7 of Conrath et al (1991) shows a weak dependence in synthetic spectra of methane cloud models in the 220 to 325 cm −1 wavenumber range where the atmosphere is tranparent enough to allow emission from the underlying clouds to contribute to the outgoing radiation field. They applied the method to Voyager IRIS spectra covering latitudes near 39-45 • S and found that radii fall between 0.3 and 30.0 µm.…”
Section: Cloud Propertiesmentioning
confidence: 99%
“…2 (digitized from Fig. 1 of Conrath et al 1991). To increase grid resolution, we reduce the physical domain size in all three directions while maintaining about the same number of grid points (Table I), and the layers are spaced proportionally to log θ instead of log p, which yields three layers (vertical index k = 6, 7, and 8 in Fig.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…to model opacity are described in et al (1998). CH 3 Be zard The mean stratospheric molecular weight adopted in our modeling is 2.39, corresponding to a He mixing ratio of 0.19 (Conrath et al 1991). Spectral radiances were calculated for disk-averaged conditions and converted to Ñuxes using a value of 3.87 arcsec2 for NeptuneÏs solid angle.…”
Section: Radiative Transfer Analysismentioning
confidence: 99%